﻿A new species of Andricus Hartig, 1840 (Hymenoptera, Cynipidae) from China, with references to DNA taxonomy and Wolbachia infection - Yin Pang; Cheng-Yuan Su; Jun-Qiao Zhu; Xiao-Hui Yang; Jia-Lian Zhong; Dao-Hong Zhu; Zhiwei Liu (ZooKeys, 2022)
In the present paper, a new species of cynipid gall wasp, Andricus elodeoides Liu & Pang, is described from several provinces in southern China. The new species is closely related to the recently redescribed A. mairei (Kieffer, 1906). In addition to differences in adult and gall morphology, the new species is also readily separated by COI sequences, with a 6.2–8.9% genetic distance between populations of the new species and those of A. mairei. A contrasting difference in sex ratios was also observed between the two species, with A. elodeoides extremely female-biased (95.5–97.8% female) while A. mairei male-biased to more balanced (5.4–43.5% female). PCR screening for Wolbachia infection further revealed contrasting infection rates between populations of A. elodeoides and A. mairei: the Wolbachia infection rate was 0% in A. elodeoides and 100% in A. mairei. Cytoplasmic incompatibility induced by Wolbachia is proposed as a potential mechanism of speciation of the sympatric A. elodeoides and A. mairei.